Development of an affordability assessment framework for defence contracts at the bidding stage - Bankole, O. O. (Cranfield University, 2011)
Defence contracting has changed from the traditional provision of spares and repairs to contracting long-term for availability and capability. In these long-term contracts, the customer decides to outsource services (that would have been provided in-house) to contractors by consenting to an arrangement whereby payment is made only for the period that the equipment is made available to satisfy the defence need. Availability contracts may last for 40 years and more, but the main defence customer (Ministry of Defence) is constantly faced with budget constraints. Therefore, it is vitally important to assess the financial viability of the customer to invest in the contractor‟s offering of availability, capability and other long-term contracts. The aim of the affordability research project is to develop an affordability assessment framework for the bidding stage of defence contracts. Thus, a close interaction with four industrial collaborators within the defence industry and the literature review revealed the need to investigate affordability from three perspectives namely, manufacturer profitability, supplier sustainability and customer affordability. In order to conduct the research, the methodology employed included the review of literature, industrial interviews, development of the affordability framework for the three perspectives, case study application and final validation. This resulted in the development of a uniquely original affordability assessment framework that consisted of four modules and an affordability management methodology. The modules provided measurement metrics for the three perspectives of affordability and guidelines for improving affordability from the perspectives. Information availability at the bidding stage was usually low which lead to uncertainty about the project; the fourth module was focused on determining the information capability of the project team. To assess the impact of uncertainty on affordability, a methodology which involved a logic (containing two aspects) was also developed and validated within this research. The framework developed was validated with three real-life case studies and the results obtained showed that the logic and content of the framework was appropriate. The benefit to industry is that the framework provides a platform for the manufacturer and customer to assess the affordability of defence project at the bidding stage and make decisions taking account of the impact of uncertainty.